One-pot solvothermal synthesis of hierarchical WO3 hollow microspheres with superior lithium ion battery anode performance. (20th August 2016) - Tong, Hui; Xu, Yingming; Cheng, Xiaoli; Zhang, Xianfa; Gao, Shan; Zhao, Hui; Huo, Lihua
Graphical abstract: Highlights: Hierarchical WO3 hollow microspheres were prepared by a one-pot solvothermal method. Most of the WO3 hollow microspheres are interconnected by sharing one wall. The formation process of the hierarchical WO3 hollow microspheres was investigated. The as-prepared WO3 electrode shows a high capacity and excellent cycle stability. The excellent performance is ascribed to its robust hierarchical hollow structure. Abstract: A one-pot and template-free solvothermal method was developed to synthesize the hierarchical WO3 hollow microspheres with porous shells. The porous shell of as-synthesize WO3 hollow microspheres are constructed from primary nanoplates clusters of 50 nm. The as-synthesize WO3 hollow microspheres are not monodisperse, and most of hollow microspheres are interconnected by sharing one wall. Importantly, the as-synthesize WO3 hollow microspheres exhibit excellent electrochemical performance. At current density of 100 mA g −1, they can deliver a specific capacity of 1700 mA h g −1 in the first discharge and retain a specific capacity of 700 mA h g −1 after 100 cycles. Meanwhile, even at a high current density of 1600 mA g −1, they also exhibit a specific capacity of 213 mA h g −1 after 500 cycles. This superior electrochemical performance of the as-synthesized WO3 hollow microspheres could be ascribed to its unique hierarchical architecture.